Silurian bentonites in Lithuania: correlations based on sanidine phenocryst composition and graptolite biozonation – interpretation of volcanic source regions - Tarmo Kiipli; Sigitas Radzevičius; Toivo Kallaste (Estonian Journal of Earth Sciences, 2014)
Integrated correlation of bentonites (altered volcanic ashes) and graptolite biozonation is presented. Detailed study of two Lithuanian drill core sections extended previous knowledge of the occurrence and composition of bentonites to the south. Identification of graptolite species allowed bentonites to be assigned their proper stratigraphical position. Silurian bentonites in Lithuania are mostly characterized by wide and very wide XRD 201 reflections of the main component of sanidine phenocrysts. Only fourteen of the 69 samples studied contained sanidine with a sharp reflection, which gave the best correlation potential. In the Lithuanian sections one bentonite was found in the Rhuddanian, five bentonites were recognized in the Aeronian, 17 bentonites in the Telychian, 26 in the Sheinwoodian, 10 in the Homerian and six in the Ludlow. All bentonites found in Lithuania are characterized by the main component of sanidine. A large number of Lithuanian bentonites are not known in Latvia and Estonia, indicating that volcanic ashes reached the East Baltic area from two source regions – the Central European and Norwegian Caledonides.